Atividade enzimática no solo e dinâmica de carbono e nitrogênio em pastos de capim-tanzânia sob índices de área foliar residual - Silva, Victor Costa e [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The production of ruminants under grazing has been identified as major contributors to emissions of environmentally thermogenic gases. However, studies show that pasture, if well managed, can become mitigating these gases. Therefore, the objective of this study was quantify the stocks of carbon, nitrogen soil, the chemical composition of litter, CO2 emission, temperature and enzyme activity in soil of pastures of tanzaniagrass subjected to different intensities of rotational grazing. The experiment was conducted at the Goat Breeding UNESP - Jaboticabal from December 2010 to May 2012. The treatments consisted of three levels of residual leaf area index (rLAI) (0.8, 1.6, 2.4) in split plot arrangement in the time with four blocks used for the tests, totaling 12 experimental units. The rLAI were measured through the canopy analyzer. The criterion for entrance of animals used was 95% (LI), remaining until the target was reached rLAI. The variables evaluated were: production of herbage mass, chemical composition of litter, carbon stocks and soil nitrogen, CO2, temperature and enzyme activity in the soil, which evaluated the enzymes cellulase, arylsulfatase and dehydrogenase. The pastures of tanzania grass were affected by increasing rLAI dry weight of stem (DHS) variable pre grazing (P=0.0353) and after grazing the dry mass of leaves (DML) increased with rising rLAI (P=0.0214). In the variable chemical composition of litter, was evaluated organic matter (OM), carbon (C), nitrogen (N), relation carbon:nitrogen (C:N), phosphorus (P) and lignin. Only phosphorus (P) showed interaction (P <0.05) between rLAI and days of incubation. For the other variables there was no effect of treatments, only incubation times were significant (P<0.05). The contents of C and N and soil C stocks and soil N had no significant effect (P> 0.05) for rLAI where only evaluated depths was significant (P <0.05), being higher in surface and decreasing in ...

A produção de ruminantes em pastagens é apontada como grande contribuinte de emissões de gases termogênicos ao meio ambiente. Porém, estudos demonstram que as pastagens, se bem manejadas, podem se tornar mitigadoras destes gases. Com isso, o objetivo desse estudo foi quantificar os estoques de carbono e nitrogênio do solo, composição química da serrapilheira, emissão de CO2, temperatura e atividade enzimática em solos de pastos de capim-tanzânia submetidos a diferentes intensidades de pastejo intermitente. O experimento foi conduzido no setor de Caprinocultura da UNESP – Jaboticabal no período de dezembro de 2010 a maio de 2012. Os tratamentos consistiram de três índices de área foliar residual (IAFr) (0,8; 1,6; 2,4), em medidas repetidas no tempo com quatro blocos utilizados para as avaliações, totalizando 12 unidades experimentais. Os IAFr foram medidos com o auxílio do aparelho analisador de dossel. O critério adotado para entrada dos animais foi 95% de interceptação luminosa (IL), permanecendo até que o IAFr alvo fosse alcançado. As variáveis avaliadas foram: produção de massa de forragem, composição química da serrapilheira, estoques de carbono e nitrogênio no solo, emissão de CO2, temperatura e atividade enzimática no solo, onde avaliou-se as enzimas celulase, arilsulfatase e desidrogenase. Nas variáveis de composição química da serrapilheira, foram avaliados os teores de matéria orgânica (MO), carbono (C), nitrogênio (N), relação carbono:nitrogênio (C:N), fósforo (P) e lignina. Os pastos de capim-tanzânia foram influenciados pelo aumento do IAFr na variável massa seca de colmo (MSC) no pré pastejo (P=0,0353) e no pós pastejo a massa seca de folhas (MSF) aumentou com a elevação dos IAFr (P=0,0214). Para a composição química da serrapilheira apenas o fósforo (P) apresentou interação (P<0,05) entre os IAFr e dias de incubação. Para as demais variáveis não houve efeito ...
Keywords: Enzimas; Dioxido de carbono; Liteira (Entulho); Solos - Teor de nitrogenio; Capim-Tanzânia; Enzymes